Burnout Assessment Tool for Students (BAT-S): evidence of validity in a Chilean sample of undergraduate university students - Carmona-Halty, Marcos; Alarcón-Castillo, Karina; Semir-González, Carla; Sepúlveda-Páez, Geraldy; Schaufeli, Wilmar B. (Frontiers in Psychology, 2024)
This brief report examines both within-network and between-network construct validity of the Burnout Assessment Tool for Students (BAT-S) in a sample of 461 Chilean undergraduate university students (70.9% female) ranging between 18 and 58 years old (M = 21.6, SD = 4.34). The reliability analysis results showed adequate internal consistency for the overall burnout score and for each dimension. In addition, confirmatory factor analysis (CFA) supported a second-order factor (academic burnout) and four first-order factors (exhaustion, mental distance, cognitive impairment, and emotional impairment) solution. Moreover, the results of multiple-group CFA supported gender invariance. Finally, structural equation model (SEM) analysis showed that academic resources and academic demands are associated with academic burnout. Overall, the BAT-S was found to be a reliable and valid tool to assess academic burnout in a sample of Spanish-speaking undergraduate university students.